Vascular phenotypes in primary non-small cell lung carcinomas and matched brain metastases. - Jubb, A; Cesario, A; Ferguson, M; Congedo, M; Gatter, K; Lococo, F; Mulè, A; Pezzella, F (2011)
BACKGROUND: Anti-angiogenic therapy with bevacizumab (an anti-vascular endothelial growth factor (VEGF) antibody) predominantly targets immature blood vessels. Bevacizumab has shown a survival benefit in non-small cell lung carcinoma (NSCLC) and has recently been demonstrated to be safe in patients with brain metastases. However, it is not known whether bevacizumab is effective against brain metastases or whether metastases are representative of their primary in terms of VEGF expression, hypoxia, proliferation and vascular phenotype. The aim of this study was to evaluate these factors in a series of matched primary NSCLCs and brain metastases. METHODS AND RESULTS: Immunohistochemistry showed strong correlation of carbonic anhydrase 9 expression (a marker of hypoxia) in primary and secondary cancers (P=0.0002). However, the proliferation index, VEGF expression, microvessel density and the proportion of mature vessels were discordant between primary and secondary cancers. The mean proportion of mature vessels was 63.2% higher in the brain metastases than the primary tumours (P=0.004). Moreover, the vascular pattern of the primary tumour was not representative of the metastasis. CONCLUSIONS: Brain metastases have a significantly higher proportion of mature vasculature, suggesting that they may be refractory to anti-VEGF therapy. These findings may have implications for clinical trials and biomarker studies evaluating anti-angiogenic agents in brain metastases.